China in Latin America: The expansion of the Silk Road - Furlong y Zacaula , Aurora (Posgrados de la División de Ciencias Económica Administrativas, 2023)
China's position as the world's leading economic power has generated a strong global demand for raw materials, which are essential to maintain its pace of industrial growth and for the construction of its most ambitious initiative, the Belt and Road Initiative (BRI). The Asian country has sought in other regions geostrategic spaces for the extraction of large volumes of natural resources, finding in Latin America a vital space for investment focused on the extraction of these resources. The objective of this paper is to analyze the impact of the New Silk Road in Latin America, due to the fact that since the CELAC summit in 2018, China has not spared in granting unpayable millionaire loans, also creating new initiatives such as the South American bioceanic corridor.